Endobronchial Closure of Bronchopleural Fistula with Amplatzer PFO Device - Krumpolcova, M.; Durand, M.; Rossi-Blancher, M.; Heylbroeck, C.; Vanzetto, G.; Albaladejo, P.; Brichon, P.-Y. (The Thoracic and Cardiovascular Surgeon, 2012)
Bronchopleural fistula (BPF) is a feared postoperative complication of pneumonectomy that carries significant morbidity and mortality. BPF can be treated by various surgical and medical techniques. Endobronchial techniques have been used for the delivery of biological glue, sealants, coils, and covered stents with variable degrees of success, depending on the size of the fistula. A recent case report described the endobronchial closure of a BPF through the implantation of an Amplatzer ASD device, commonly used for transcatheter closure of atrial septal defects. In this case report, we describe closure of a BFP using the Amplatzer PFO device.
Keywords: thoracic surgery; complications; airway; ventilation; bronchial disease; amplatzer; bronchopleural fistula; endobronchial closure